Alteraciones hematológicas asociadas al déficit de hierro en adolescentes embarazadas del cantón Guano - Provincia de Chimborazo periodo enero-septiembre 2024. - Oñate Chávez, Cristhian Javier (2025)
Adolescent pregnancy is one of the most prominent issues affecting millions of people worldwide. It is estimated that approximately 25% of this population get pregnant. The root of adolescent pregnancy is associated to socioeconomic, educational and cultural factors, with a higher prevalence in communities with limited access to health information and resources. From the physiological point of view, adolescent pregnancy implies adaptations in the hematological system, increasing the risk of anemia and other obstetric complications. The aim of the current study was to evaluate hematological alterations associated with iron deficiency in pregnant adolescents in the Guano Canton – Chimborazo Province from January to September 2024. The main beneficiaries of this study were young pregnant women aged 13 to 19 who resided in Guano. The methodology applied was a nonexperimental, prospective and descriptive cross-sectional field study. The selected population was 66 adolescents, managing to work with a sample of 20 pregnant women, who met the inclusion criteria within the established period. The results obtained showed that there is a considerable index of pregnant women who showed hematological alterations with iron deficiency, representing a quarter of the total sample studied, who presented microcytic hypochromic anemia. In contrast, the rest-maintained values within normal ranges. In the same way, it was possible to demonstrate the prevalence in this population, representing the percentage of adolescents who suffer hematological variations due to iron deficiency during their pregnanc.